Insights into the role of intracellular calcium signaling in the neurobiology of neurodevelopmental disorders - Klocke, Benjamin; Krone, Kylie; Tornes, Jason; Moore, Carter; Ott, Hayden; Pitychoutis, Pothitos M. (Frontiers in Neuroscience, 2023)
Calcium (Ca2+) comprises a critical ionic second messenger in the central nervous system that is under the control of a wide array of regulatory mechanisms, including organellar Ca2+ stores, membrane channels and pumps, and intracellular Ca2+-binding proteins. Not surprisingly, disturbances in Ca2+ homeostasis have been linked to neurodegenerative disorders, such as Alzheimer’s and Parkinson’s diseases. However, aberrations in Ca2+ homeostasis have also been implicated in neuropsychiatric disorders with a strong neurodevelopmental component including autism spectrum disorder (ASD) attention-deficit hyperactivity disorder (ADHD) and schizophrenia (SCZ). While plasma membrane Ca2+ channels and synaptic Ca2+-binding proteins have been extensively studied, increasing evidence suggests a prominent role for intracellular Ca2+ stores, such as the endoplasmic reticulum (ER), in aberrant neurodevelopment. In the context of the current mini-review, we discuss recent findings implicating critical intracellular Ca2+-handling regulators such as the sarco-ER Ca2+ ATPase 2 (SERCA2), ryanodine receptors (RyRs), inositol triphosphate receptors (IP3Rs), and parvalbumin (PVALB), in the emergence of ASD, SCZ, and ADHD.